For There to Be Meaning, There Must Be Fiction - Jevsejevas, Paulius (Colloquia, 2017)
Nijolė Keršytė, Pasakojimo pramanai: Monografija, Vilnius: Vilniaus universiteto leidykla, 2016, 496 p., ISBN 978-609-459-798-5